Revisiting the mechanism of hypoxic pulmonary vasoconstriction using isolated perfused/ventilated mouse lung. (1st November 2020) - Jain, Pritesh P.; Hosokawa, Susumu; Xiong, Mingmei; Babicheva, Aleksandra; Zhao, Tengteng; Rodriguez, Marisela; Rahimi, Shamin; Pourhashemi, Kiana; Balistrieri, Francesca; Lai, Ning; Malhotra, Atul; Shyy, John Y.‐J.; et al.
Abstract : Hypoxic Pulmonary Vasoconstriction (HPV) is an important physiological mechanism of the lungs that matches perfusion to ventilation thus maximizing O2 saturation of the venous blood within the lungs. This study emphasizes on principal pathways in the initiation and modulation of hypoxic pulmonary vasoconstriction with a primary focus on the role of Ca 2+ signaling and Ca 2+ influx pathways in hypoxic pulmonary vasoconstriction. We used an ex vivo model, isolated perfused/ventilated mouse lung to evaluate hypoxic pulmonary vasoconstriction. Alveolar hypoxia (utilizing a mini ventilator) rapidly and reversibly increased pulmonary arterial pressure due to hypoxic pulmonary vasoconstriction in the isolated perfused/ventilated lung. By applying specific inhibitors for different membrane receptors and ion channels through intrapulmonary perfusion solution in isolated lung, we were able to define the targeted receptors and channels that regulate hypoxic pulmonary vasoconstriction. We show that extracellular Ca 2+ or Ca 2+ influx through various Ca 2+ ‐permeable channels in the plasma membrane is required for hypoxic pulmonary vasoconstriction. Removal of extracellular Ca 2+ abolished hypoxic pulmonary vasoconstriction, while blockade of L‐type voltage‐dependent Ca 2+ channels (with nifedipine), non‐selective cation channels (with 30 µM SKF‐96365), and TRPC6/TRPV1 channels (with 1 µM SAR‐7334 and 30 µM capsazepine, respectively) significantly and reversibly inhibited hypoxic pulmonary vasoconstriction. Furthermore, blockers of Ca 2+ ‐sensing receptors (by 30 µM NPS2143, an allosteric Ca 2+ ‐sensing receptors inhibitor) and Notch (by 30 µM DAPT, a γ‐secretase inhibitor) also attenuated hypoxic pulmonary vasoconstriction. These data indicate that Ca 2+ influx in pulmonary arterial smooth muscle cells through voltage‐dependent, receptor‐operated, and store‐operated Ca 2+ entry pathways all contribute to initiation of hypoxic pulmonary vasoconstriction. The extracellular Ca 2+ ‐mediated activation of Ca 2+ ‐sensing receptors and the cell–cell interaction via Notch ligands and receptors contribute to the regulation of hypoxic pulmonary vasoconstriction.